Dual functional sp2 carbon-conjugated covalent organic frameworks for fluorescence sensing and effective removal and recovery of Pd2+ ions. Issue 47 (24th November 2021) - Yue, Jie-Yu; Ding, Xiu-Li; Wang, Yu-Tong; Wen, Yang-Xin; Yang, Peng; Ma, Yu; Tang, Bo
Abstract : The effective detection and simultaneous removal of Pd 2+ is beneficial to environmental protection as well as human health, and owing to its high consumption and cost, the recovery of Pd 2+ is important to ensure sustainability. Abstract : The effective detection and simultaneous removal of Pd 2+ is beneficial to environmental protection as well as human health, and owing to its high consumption and cost, the recovery of Pd 2+ is important to ensure sustainability. Herein, an sp 2 carbon-conjugated covalent organic framework containing a selenodiazole structure (PY-SE-COF) was synthesized for the first time and explored for fluorescence detection and the effective removal and recovery of Pd 2+ ions. PY-SE-COF has vinylene linkages from the Knoevenagel reaction, with strong fluorescence and good chemical stability in a wide pH range. PY-SE-COF is specific to Pd 2+ with high selectivity and a detection limit of 0.45 μM. Simultaneously, PY-SE-COF can remove Pd 2+ from aqueous solution effectively with high selectivity as shown by the pseudo-second-order kinetic model ( R 2 > 0.9999) and fits well with the Freundlich adsorption model ( R 2 = 0.9727). After 10 consecutive adsorption–desorption cycles, the removal efficiency of Pd 2+ by PY-SE-COF is still higher than 95%. Our results demonstrate that sp 2 COFs are a powerful and promising platform for structural design towards the simultaneous monitoring and removal of various types of environmental contaminants.